Perlindungan Hukum Terhadap Anak Terlantar Ditinjau Dari UU No.35 Tahun 2014 Tentang Perubahan Atas UU No. 23 Tahun 2002 Tentang Perlindungan Anak - Hafizhah Khairannisa; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The problem of abandoned children has become problem that never ends. A neglected child is a child who does not receive proper care, protection and nurturing, both physically, mentally and socially. Child neglect occurs due to the inability of family or guardians carry out their obligations in the process of fulfilling children's rights. The impact of child neglect is that children often drop out of school, get involved in child labor, and end up in situations of neglect. in child labor, and end up in dangerous situations such as violence and exploitation. This research aims to find out, analyze, and describe the legal protection of neglected children in terms of Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection and government efforts to fulfill the rights of neglected children. The research method uses juridical law normative and using a statutory approach. Research results The results show that the state guarantees and provides legal protection related to the rights of neglected children through Law Number 35 Year 2014 Regarding the Amendment to Law Number 23 Year 2002 Regarding Child Protection and the government make various efforts to ensure the fulfillment of children's rights, including neglected children.